[Marketing Papers] - Spence, Mark T. (Fall;Marketing., 1999)
Keywords: dept.mkt; faculty_collection; sabbatical_report

Examining the longevity of new agency accounts: A comparative study of U.S. And U.K. Advertising experiences - Davies, M.; Prince, M. (Journal of Advertising, 1999)
Since the typical account longevity is short, agencies should anticipate their likelihood of loss, seek to forestall and invest in their client relationships. A model is proposed for examining account lifetimes, which can offer guidance on the likely retention of future accounts. The impact of agency structural characteristics on longevity is also examined, and compared for both U.S. and U.K. markets. Results for both markets indicate that cumulative account dissolution increases at a decreasing rate over time. Greater account longevity is associated with larger agency size (both in terms of agency billings and employees), and agency age but not with stability of billings growth. Evidence suggests that several structural characteristics of agencies reflect the motivation and/or ability to maintain accounts. © 1999 Taylor & Francis Group, LLC.
Keywords: dept.mkt